Rabbi Yapheth Abou Aly ibn Aly Bassorensis Karaitarum doctoris in Canticum canticorum commentarium Arabicum. - Japheth ben Ali, ha-Levi, active 10th century; Bargès, J. J. L. (Jean Joseph Léandre), 1810-1896 (Lutetiæ Parisiorum : [publisher not identified], 1884)
quod ... edidit atque in linguam latinam transtulit J. J. L. Bargès. [With the Hebrew text.].
Reproduction of the original from The British Library.
Includes index.
Text in Latin, Arabic and Hebrew ; translated from the original Arabic.
Electronic reproduction.
Keywords: Bible. -- Commentaries; Christianity